2001
DOI: 10.2307/2657115
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome studies: Mexican Compositae

Abstract: Chromosome observations reported here from 70 collections representing 65 species from 40 genera of Compositae (mostly Heliantheae) provide taxonomically useful information. First counts for 28 species, including the first count for Psacaliopsis, may prove to be especially interesting in relation to phyletic and taxonomic alignments of the taxa. Of special interest among first reports is 2n ϭ 5 II for Stevia lita; other stevias have x ϭ 11, 12, or 17. Thirteen of our counts differ from prior reports and may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Therefore, although only diploid (n 5 11) specimens of Pr. macrocephalum have been found in Chiapas (Strother, 1983) and Arizona (Keil & Pinkava, 1976), Pr. ruderale of South America has diploid and tetraploid (and possibly hexaploid) members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although only diploid (n 5 11) specimens of Pr. macrocephalum have been found in Chiapas (Strother, 1983) and Arizona (Keil & Pinkava, 1976), Pr. ruderale of South America has diploid and tetraploid (and possibly hexaploid) members.…”
Section: Discussionmentioning
confidence: 99%
“…Pectis species have traditionally been considered a natural, morphologically distinctive group (Strother, 1977). However, molecular analysis of the Tageteae (Loockerman et al, 2003) showed Pectis linifolia as sister to the combined Pectis+Porophyllum, based on a combined ITS+ndhF dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome counts provide indispensible information on genetic discontinuities within and among species, and they contribute to our understanding of phylogenetic relationships at all taxonomic levels (e.g., Semple et al, 1989;Pinkava et al, 1992;Baldwin et al, 2002). Realizing the value of chromosome data for evolutionary studies, systematists have pursued the long-term goal of determining chromosome numbers for as many species and populations as possible (Carr et al, 1999;Strother and Panero, 2001). Ubiquitous or economically important families such as Asteraceae and Poaceae have benefited greatly from this attention, but many other groups remain undersampled.…”
mentioning
confidence: 99%
“…Ray ovaries trigonal, 2.5-3.7 mm long, glabrous or sparsely pubescent, pappus of 3 squamellae or absent. Chromosome number x = 17 Schilling & Panero, 1990;Strother & Panero, 2001).…”
Section: Discussionmentioning
confidence: 99%